2021
DOI: 10.1186/s13046-021-01980-0
|View full text |Cite
|
Sign up to set email alerts
|

TRIM37 orchestrates renal cell carcinoma progression via histone H2A ubiquitination-dependent manner

Abstract: Background Ubiquitylation modification is one of the multiple post-transcriptional process to regulate cellular physiology, including cell signaling, cycle regulation, DNA repair and transcriptional regulation. Members of TRIM family proteins could be defined as E3 ubiquitin ligases as they contain a RING-finger domain, and alterations of TRIM proteins are involved into a broad range of diverse disorders including cancer. TRIM37 is a novel discovered E3 ubiquitin ligase and acts as a oncoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…TRIM37 is dysregulated in RCC, and its increased expression is associated with aggressive neoplastic phenotypes and poorer survival. Mechanistically, TRIM37 promotes the malignant progression of RCC via TGF-β1/SMAD signaling through its direct mediation by ubiquitinating-H2A modifications ( 31 ). Taken together, these findings indicate that TRIM proteins are associated with the occurrence and development of RCC and are potential biomarkers for prognostic prediction.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM37 is dysregulated in RCC, and its increased expression is associated with aggressive neoplastic phenotypes and poorer survival. Mechanistically, TRIM37 promotes the malignant progression of RCC via TGF-β1/SMAD signaling through its direct mediation by ubiquitinating-H2A modifications ( 31 ). Taken together, these findings indicate that TRIM proteins are associated with the occurrence and development of RCC and are potential biomarkers for prognostic prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The study design and protocol were approved by the ethic committee of hospital. IHC staining was performed as previously described [ 32 , 33 ]. Briefly, the primary antibody was incubated as follows: anti-HNRNPC (Proteintech, 1: 200, China).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study also confirmed this conclusion in RCC tumors. Moreover, the upregulated expression of TRIM37 could predict aggressive neoplastic phenotypes [ 39 ]. In addition, knockdown of TRIM11 suppressed the tumorigenicity of chordoma cells [ 130 ].…”
Section: The Trim Family and Cancer Pathologymentioning
confidence: 99%
“…TRIM47 also physically interacts with SMAD4, increasing its ubiquitination and degradation [ 215 ]. TRIM37 promotes RCC cell EMT and malignant progression through TGF-β signaling activation, as a consequence of TRIM37 mediated H2A ubiquitination modification [ 39 ]. TRIM59 was found to downregulate the protein expression of p-SMAD2 and thus inhibit the activity of the TGF-β signaling pathway [ 216 218 ].…”
Section: The Trim Family and Cancer Pathologymentioning
confidence: 99%